2004
DOI: 10.1111/j.1365-2354.2003.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and outcome of 93 cases of craniopharyngioma

Abstract: We studied a series of 93 patients diagnosed with craniopharyngioma during a 15-year period with respect to presenting symptom, clinical course and management. The majority (62%) of patients were men, and had presented with neurological symptoms (75%), with headaches (82%) being the most common presenting symptom. The incidence of certain endocrine and ophthalmic symptoms varied little from that in the literature, on the other hand, the incidence of certain other symptoms did differ markedly from the literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 19 publications
0
22
1
Order By: Relevance
“…Eight reports described whether approval from an ethics committee was obtained [5960, 64, 66, 69–71, 75]. The majority (58.3%) of patients described in the articles was male [38, 41–50, 52, 56–57, 6061, 63–64, 67–68, 72–75]. We were unable to determine the number of patients who were children, as most of the reports did not include this information.…”
Section: Resultsmentioning
confidence: 99%
“…Eight reports described whether approval from an ethics committee was obtained [5960, 64, 66, 69–71, 75]. The majority (58.3%) of patients described in the articles was male [38, 41–50, 52, 56–57, 6061, 63–64, 67–68, 72–75]. We were unable to determine the number of patients who were children, as most of the reports did not include this information.…”
Section: Resultsmentioning
confidence: 99%
“…This is higher in children with craniopharyngiomas where an incidence of 72-95% can be found on provocative testing [4,5,6,7,8,9,10]. Growth deceleration is one of the commonest findings in children but is often recognized only retrospectively, as presentation with growth failure is less common [3]. As the need for urgent surgical intervention for raised intracranial pressure takes priority at diagnosis, there is less opportunity to make a diagnosis of growth hormone deficiency via provocative testing, in which case the measurement of a baseline insulin-like growth factor-1 level can be helpful.…”
Section: Pre-operative Overviewmentioning
confidence: 99%
“…Other tumours are functioning and non-functioning pituitary adenomas, germinomas and non-germinomatous germ cell tumours, Langerhans cell histiocytoses, chiasmatic (low-grade) gliomas, suprasellar arachnoid cysts and hypothalamic-pituitary astrocytomas [1]. These tumours present with acute or more insidious compression symptoms of adjacent neural structures leading to a raised intracranial pressure with hydrocephalus in 50%, visual impairment in 38% and endocrine abnormalities in 66-77% of cases [1,2], with a higher incidence in craniopharyngiomas than in the other tumour types [2,3,4,5]. Although symptoms due to neuroendocrine dysfunction may not be obvious at presentation [6], clinical features of endocrinopathies are frequently found on careful assessment and have often been present for months or years prior to presentation.…”
Section: Pre-operative Overviewmentioning
confidence: 99%
“…Several authors have reported high recurrence rates despite apparently complete tumor resection and negative postoperative brain imaging, providing another strong argument for the concept of limited surgery combined with other therapeutic approaches, such as radiotherapy or intracystic catheter placement. 2,3,30,37,42,43,50,62,68,71,78,83,84,89,92,98 The surgical routes used to remove craniopharyngiomas have previously been transcranial approaches, whereas the transsphenoidal approach, in accordance with the indications defined by Guiot and Derome 35 in the early 1960s, was proposed initially for infradiaphragmatic lesions, with an enlarged sella, preferably in patients who had already developed panhypopituitarism. 72 More recently, technological progress and advances in terms of visualization permitted the extension of the microscopic transsphenoidal approach to a variety of suprasellar lesions.…”
mentioning
confidence: 99%